Evaluation of efficacy of GCSF in reducing neutropenia among carcinoma patients undergoing anti-cancer chemotherapy. A prospective cohort study - Maria Kakar; Sami Ullah; Amjad Khan; Shabnam Nazir (PLoS ONE, 2025)
The use of granulocyte colony-stimulating factor (GCSF) to control febrile neutropenia (FN) caused by anti-cancer chemotherapy is well documented but it still needs to evaluated with respect to the specific type of cancer and chemotherapeutic agents. The present study evaluates the efficacy of adjunctive GCSF for treating FN after taking anticancer therapy by measuring clinical, hematological and microbiological outcomes. It is a single center study conducted at Hayatabad Medical Complex (HMC), Peshawar, Pakistan. Adult patients of both genders, suffering from different types of sarcomas and taking anticancer chemotherapy were included in the study. The study was conducted between January 2023 and January 2024. Baseline data including demographic data, medication history and hematological evaluation of all the patients was recorded at the time of enrolment. Primary outcomes of the study were the extent of absolute neutrophil count (ANC) recovery, duration and severity of neutropenia (grade IV), period to fever resolution. After the therapy (with and without adjunctive GCSF) clinical outcomes, hematological evaluation and microbiological data was compared and evaluated. All the data was statistically analyzed by SPSS (IBMS, version 20). A total number of 120 patients were investigated out of which data of 109 patients was included. Out of 109 patients, 64 (58.72%) received adjunctive GCSF therapy, and 45 (41.28%) did not receive adjunctive GCSF. Comparison of the data showed that the patients receiving adjunctive GCSF had a significant improvement ANC recovery time, better recovery of fever and patients were free of infections. This study concluded that adjunctive GCSF therapy benefits the patients undergoing anticancer treatment for different types of carcinoma.